Ecological Thinking and Certification of Hotel Service Providers in Slovakia - TIMČÁK, Gejza Mikuláš; JABLONSKÁ, Jana; MIXTAJ, Ladislav; ŠTRBA, Ľubomír; DERCO, Ján; WEISS, Erik (Journal of Environmental Management and Tourism, 2016)
One of the major areas, where sustainability is a very important issue is the hotel industry. Presently there are a number of projects – some spearheaded by NGOs, some by professional or governmental bodies – which audit hotels and lodging providers from the point of view of sustainability and “green” performance. The paper analyses the approach of the hotel industry, as well as clients to “greening”. The perception of ecofriendliness varies, however from culture to culture. The paper analyses the case of environmental awareness of hospitality service providers 3 and 4 star hotels and their attitude towards “green” performance in one of the emerging tourism destinations - Slovakia.
Keywords: hospitality; greening; ecological awareness; eco-labelling; Slovakia